Social entrepreneurship: intentions and barriers to entry in South Africa - Aldridge, Matthew (My University, 2018)
Social entrepreneurial intentions are influenced by different antecedents to those of general, or opportunity entrepreneurs. The purpose of this study was to investigate and analyse the effect of previously identified barriers to entry on social entrepreneurial intentions in South Africa. The Theory of Planned Behaviour has been adopted as the theoretical background. Empirical data was collected through online surveys from potential social entrepreneurs in South Africa. The data was analysed using descriptive statistics, exploratory factor analysis, reliability analysis and multiple regression. The results of the factor analysis led to two hypotheses being removed from the study. The remaining three hypotheses that were tested were related to capital, skill and risk related barriers to entry. The findings indicated that there was no significant relationship between these barriers to entry and social entrepreneurial intentions. It was concluded that due to the difference in motivational antecedents, social intentions are not impacted by these barriers which have been identified as relevant barriers for opportunity entrepreneurs.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management in the field of Entrepreneurship and New Venture Creation Johannesburg, 2018
Keywords: Social entrepreneurship; Sustainable development